Medical Education by Modeling Biological Issues of Students (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today, the main goal of the “National Personnel Training Program” is the formation of young, knowledge-hungry, free-thinking, advanced, leading youth.